Transcatheter valve in valve replacement in stentless prosthetic aortic valves compared to a surgical approach: The lunch is good, but not free!. Issue 1 (7th January 2022) - Inci, Errol; Block, Peter C.
Key Points: Particularly in a higher risk population, transcatheter aortic valve in valve replacement is a suitable alternative to repeat surgical valve replacement—with possibly better short term outcomes. Challenges remain: Valve‐in‐valve TAVR may require a second valve placement and has more residual valve leak than surgery. Long‐term clinical outcomes comparing transcatheter and surgical replacements for degraded stentless aortic valves are still needed.